Religious marriage between consent and coercion - Bazić, Jovan R (Sociološki pregled, 2021)
The review of this monograph is observed through the analytical-descriptive approach, which considers the social context of religious marriage arrangement. Moreover, special attention is paid to the results of the analysis of the church matrimonial law rules and their effect in Serbia’s legal system, as well in some European societies. The review also speaks about the arrangement of LGBT partnerships as a challenge to the traditional marriage concept.
Keywords: religious marriage; religion; right; LGBT partnership